Model Rebels : The Rise and Fall of China's Richest Village - Gilley, Bruce, 1966- (Book collections on Project MUSE., 2001)
This is the chronicle of a village on the northern China plains during the post-1978 economic reforms. It examines how Daqiu Village led by Yu Zuomin, a Communist Party secretary and president of the local industrial conglomerate, became the richest village in China and a model for the rural reforms of the 1980s and early 1990s.